Pemilahan Sampah Dan Pemanfaatan Limbah Kertas Sebagai Edukasi Zero Waste Lifesyle Menuju Wairausaha Berbasis Lingkungan - Ika Zutiasari; Wening Patmi Rahayu; Raisa Fitri; Jefry Aulia Martha (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The purpose of this service program is to provide knowledge and skills related to processing waste, especially paper/inorganic waste into products that have a sale value. Participants in this program are 20 fostered residents from Class 1 prisons in Malang. The method of implementing this activity is carried out by providing guidance, in the form of providing material, demonstrations to direct practice. As a result of this training activity, participants can develop products such as vases, tissue boxes, bags, etc. from the rolls of paper they make. The participants were very enthusiastic in implementing the program, because this program is in line with previous programs related to waste management as a zero waste lifestyle education.